MANAJEMEN KEUANGAN ALA RASULALLAH SAW DAN PARA SAHABAT DALAM BERDAKWAH - Moh. Asep Zakariya Ansori (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2023)
This paper discusses the Financial Management Ala Rasulallah Saw and the Companions so that they can be used for preaching to spread Islam. financial management is carried out to organize a fair and solid economic order of society so that the prophet's preaching mindset is not only through war and bloodshed but through good management and management. Balanced and transparent management of state revenues and expenditures is one of the policies that must be carried out to maintain the welfare of the community. The purpose of this paper is to review the management and economic policies that have been made by Rasulallah Saw so that they can be applied in the present. The method used in this writing is qualitative, namely by analyzing various reading literature and drawing a conclusion